MITIGASI BENCANA LONGSOR DI KECAMATAN LUBUK BEGALUNG - Selvy Meidela Putri; Dedi Hermon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the level of landslide vulnerability and how community-based landslide mitigation is carried out in Lubuk Begalung District. This study uses a quantitative descriptive approach. The results of this study indicate that the area with low landslide vulnerability is 1,251.47 hectares, moderate vulnerability is 1,113.24 hectares, and high vulnerability is 512.19 hectares. In the implementation of community-based landslide mitigation in the high landslide vulnerability zone, there is the highest level of involvement in all stages of mitigation. The community in this area is active in observing environmental conditions, participating in training, planting trees, and building retaining walls. In the moderate risk zone, there is sufficient involvement in the implementation stage, such as reforestation and information dissemination, but it is still low in the aspects of planning and evacuation simulation. Conversely, communities in low-risk zones show almost no mitigation activities, whether in the form of risk identification, planning, or implementation.